The impact of economic variable on exchange rate in Malaysia / Mohamad Hasraf Mohamad Azmi and Shamsul Anuar Hasshim - Mohamad Azmi, Mohamad Hasraf; Hasshim, Shamsul Anuar (Faculty of Business and Management, 2016)
The objective of this study is to examine the relationship between gross domestic product, inflation rate, interest rate and balance of payment to exchange rate in Malaysia. The study used Simple Linear Regression and Multiple Linear Regression in order to find relationship among the variables. The quarterly data for exchange rate, gross domestic product, inflation rate, interest rate and balance of payment are collected from 2008 to 2015. From the result, it reveals that all the variables have significant positive and negative relationship towards exchange rate in Malaysia. It means that there are impact in changes of economic variable towards exchange rate. These result further our understanding of the relationship between all the variables and should be useful for regulator, investor and speculator.